PERSEPSI MAHASISWA AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA - - Rusmanto; Ida Mentayani; Sri Novi Yani (Master of Accounting Universitas Trunojoyo Madura, 2014)
This aimed of this research to determine whether there are differences in perception between accounting student community college accounting students and private universities in The Indonesian Institute of Accountant Ethical Code. Testing research hypotheses using independent sample t-test using SPSS 17 (Statistical Packages for Social Science).The results of the research indicate t value of 2.072 with a significance of 0.039. With a significance value smaller than 0.05, it means it can be concluded that there is a difference between the perception of college accounting students and private universities to the code of ethics accountant. Students accounting public universities have the perception that a little better because it has a mean value of 87.96 while accounting students private universities have a mean value of 85.94. The difference was due to the teaching methods employed by each college is different, so understanding and views of college students in accounting, both public and private sectors have different perceptions of the code of ethics accountant